Teaching Reading Comprehension: A Pre-experimental Research of Story Mapping Strategy - Wahyu Purnomo; Ardayati Ardayati; Ani Fiani (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research was aimed to prove that it was significantly effective to teach reading comprehension by using story mapping strategy of narrative text to the tenth grade students of MAN 2 Lubuklinggau. This research used a pre-experimental design with one group pre-test and post-test. The population of this research was the tenth grade students of MAN 2 Lubuklinggau that consisted of 288 students. The sampling technique used was cluster random sampling with the method of paper roll and the sample selected was X 2 class consisted 35 students. The data for this research was collected by using a multiple choice test. The result of this research proved there was significant difference between the mean score in the pre-test and post-test. The students mean score in the pre-test was 68.45 and in the post test was 77.25. The t-obtained was 5.86, it was higher than 1.699 as the critical value in t-table. Finally, the researcher found that Teaching Reading Comprehension by using Story Mapping Strategy to the Tenth Grade Students at MAN 2 Lubuklinggau was effective. Therefore, it was clearly stated that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected.